Survival Implications of Thrombus Recurrence or Bleeding in Cancer Patients Receiving Anticoagulation for Venous Thromboembolism Treatment - McBane II, Robert D.; Vlazny, Danielle T.; Houghton, Damon; Casanegra, Ana I.; Froehling, David; Daniels, Paul; Riaz, Irbaz bin; Hodge, David O.; Wysokinski, Waldemar E. (Thrombosis and Haemostasis, 2022)
Background Study aims were to analyze prospectively collected data from patients with cancer-associated venous thromboembolism (VTE) to determine the impact of VTE recurrence and anticoagulant-related bleeding on all-cause mortality.Patients/Methods Consecutive cancer patients with acute VTE treated with anticoagulants (March 1, 2013–November 30, 2021) were included in this analysis. Anticoagulant therapy-associated VTE recurrences, major bleeding, and clinically relevant nonmajor bleeding (CRNMB) were assessed for their impact on all-cause mortality outcomes.Results This study included 1,812 cancer patients with VTE. Of these, there were 97 (5.4%) with recurrent VTE, 98 (5.4%) with major, and 104 (5.7%) with CRNMB while receiving anticoagulants. Recurrent VTE (hazard ratio [HR]: 1.52; 95% confidence interval [CI]: 1.16–2.00; p = 0.0028), major bleeding (HR: 1.82; 95% CI: 1.41–2.31; p = 0.006), and CRNMB (HR; 1.38; 95% CI: 1.05–1.81; p = 0.018) each adversely influenced mortality outcomes. Deep vein thrombosis as the incident thrombotic event type was associated with VTE recurrence (HR: 1.78; 95% CI: 1.08–2.89; p = 0.02). Neither cancer type nor stage, chemotherapy, or Ottawa risk category influenced VTE recurrence. Higher body weights (HR: 1.01; 95% CI: 1.00–1.01; p = 0.005) were associated with increased major bleeding, while high Ottawa scores (HR: 0.66; 95% CI: 0.46–0.96; p = 0.03) and apixaban treatment (HR: 0.62; 95% CI: 0.45–0.84; p = 0.002) were associated with fewer major bleeding outcomes.Conclusion Among cancer patients receiving anticoagulant therapy for VTE, adverse outcomes such as VTE recurrence, major bleeding, or CRNMB increase mortality risk by 40 to 80%. Identifying variables predicting these outcomes may help risk-stratify patients with poor prognosis.
Keywords: cancer; venous thromboembolism; anticoagulants; major bleeding; clinically relevant nonmajor bleeding; mortality